2011
DOI: 10.4103/0970-9290.84281
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of human telomerase reverse transcriptase in oral cancer and pre-cancer

Abstract: There was increased expression of hTERT protein in OSCC and leukoplakia samples when compared to normal oral mucosa. The cellular localization, LI and LS in OSF were significantly different from OSCC and leukoplakia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Use of IHC is a useful, reliable method of localizing the hTERT protein in tissue sections. [ 12 15 ] Telomerase activity is conventionally studied using modified polymerase chain reaction, the telomeric repeat amplification protocol assay. This technique does not permit cellular localization of telomerase activity which is better demonstrated with techniques likes IHC/ in situ hybridization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of IHC is a useful, reliable method of localizing the hTERT protein in tissue sections. [ 12 15 ] Telomerase activity is conventionally studied using modified polymerase chain reaction, the telomeric repeat amplification protocol assay. This technique does not permit cellular localization of telomerase activity which is better demonstrated with techniques likes IHC/ in situ hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…Telomerase activity is up-regulated in many tumors and studies have shown that increased telomerase expression is an early event in oral carcinogenesis. [ 7 8 9 10 11 12 13 14 ] The aim of our study was to ascertain the expression of hTERT as an indicator of telomerase activity in oral epithelia dysplasia and oral squamous cell carcinoma (OSCC) using immunohistochemistry (IHC) on formalin-fixed paraffin-embedded tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The malignant transformation rate for leukoplakia ranges from 15% to 20%, while transformation rates as high as 7.6% over a 10‐year period have been reported for OSF . Many markers including cytokeratins and human telomerase reverse transcriptase (hTERT) have been studied and found to be altered in malignant transformation …”
Section: Introductionmentioning
confidence: 99%
“…Detection of the telomerase activity in tissue by immunohistochemical methods is recent and reliable method in human tumors. Telomerase expressed in cytoplasm and nucleus of the tumoral cells [38][39][40] . In this study we used this technique in ENA and our results showed that telomerase expression in tumor tissue was increased compared to normal nasal tissue.…”
Section: Discussionmentioning
confidence: 99%